Effect of the size of the seeds of the main and second cob of maize hybrid Maxima on physiologic quality of seeds being dried by dryer and air-dried - Zahra Radmanesh; Samad Mobasser (علوم و فناوری بذر ایران)
This study was aimed to determine the effect of seed size of the first (main) ear and the second ear and drying methods on seed quality of maize hybrid Maxima. For this purpose, two different experiments, including seed production field and laboratory experiment were conducted in 2014 and 2015, in Karaj. Six rows of maternal line and two rows of paternal line were planted in seed producing field in Shahid Motahari research Station in Sugar Beet Seed research Institute. The second experiment was conducted in qualified seed testing laboratory in SPCRI. The treatments composed of two levels of seed size (7mm and 6mm), two ears position (the first (main) and the second) and two drying methods (air drying and artificial drying). Results showed that the interaction of ear position, seed size and drying methods was significant for GP, GMD, Allometric index, SL, RWW, HW and Alpha-amylase activity. Maximum and minimum of seedling length was 34.48 cm and 30.42 cm respectively and related to seed size of 7 mm of the main ear. Moreover, maximum of germination percentage was 100% that related to seed size of 7mm and 6mm of the first ear which dried by dryer, while minimum value was 83% that related to seed size of 6mm of air dried ears. According to the results of this experiment it seems that seeds of maize hybrid Maxima of 7 mm that were dried by dryer machine because of priority of germination traits are more suitable for cultivation.